Fiksi Hukum: Idealita, Realita, dan Problematikanya di Masyarakat - Hamdani, Fathul; Awang Maha Putra, Eduard; Apriliana Akbar, Dinul; Puji Pangastuti, Diah; Khairul Anam, Fathul; Putra, Eduard Awang Maha; Akbar, Dinul Apriliana; Pangastuti, Diah Puji; Anam, Fathul Khairul (Primagraha Law Review, 2023)
Legal fiction is required to foresee the possibility of those who deny law enforcement because they do not know the law. This is founded on the qualities of normative legislation, which truly relates to a prescriptive level in terms of its construction. However, many individuals are unaware of the existence of a good rule due to a lack of government socialization and a lack of knowledge on the part of the people affected. This study aims to examine how legal fiction is at an ideal level, its reality in society, and its problems. This study applies normative legal research methods, using statutory, conceptual, and case approaches. The study's findings indicate that without the theory/principle of legal fiction, many individuals are likely to avoid the snares of rules and regulations. However, because many individuals break the law, judges must be extremely prudent in their decision-making. Furthermore, to develop a solid legal system, the government must continue to maximize the distribution or dissemination of laws and regulations, including the community in the formation of laws and regulations, and raise public awareness.